THE ROLE OF JOB BURNOUT AND SOCIAL SUPPORT ON THE EFFECT OF JOB DEMAND TO EMPLOYEE PERFORMANCE - Firdaus, Ema Zahra; Noermijati, Noermijati; Ratnawati, Kusuma; Zaroug, Yousef Ali Mohamed (Universitas Brawijaya, Indonesia, 2023)
This study was conducted using the job demand-resource model to examine the effects of job demand, job burnout, and the role of social support as a measure of job resources in enhancing the influence of job demand on employee performance. Through 131 responses from the questionnaire survey, this study uses the responses obtained from a state-owned banking agency in Malang, Indonesia. Data analysis was performed using partial least square (PLS) with the WarpPLS.7.0 program and Sobel Test to verify the relationship between variables. The results of this study do not totally support the hypothesis since employee performance can be directly influenced by the degree of job demand that employees experience but not by the degree of job burnout that banking employees experience. As opposed to that, a high job demand also has a direct impact on an employee's job burnout. Another significant finding from this research is that social support has a role in enhancing the influence of job demands on employee performance, rather than mediating it. This research provides enlightenment for the banking industry regarding the importance of paying attention to employees' social support. High job demand causes a decrease in employee performance; with good social support, employees will be helped meet the job demand so that it does not impact the performance they are building. It is challenging to lessen how much job demand influences employee burnout. Banking institutions can work to provide social support while also attempting to alter employees' perceptions of their jobs' obligations. In order to successfully prevent job burnout syndrome in employees and reduce negative effects brought on by job pressures, banking leaders should provide assistance and demonstrate excellent leadership. This strategy ought to considerably lessen job burnout and directly result in improved performance.